Hydroxychloroquine attenuates autoimmune hepatitis by suppressing the interaction of GRK2 with PI3K in T lymphocytes - Jin, Chao; Gao, Bei-Bei; Zhou, Wen-Jing; Zhao, Bao-Jing; Fang, Xing; Yang, Chun-Lan; Wang, Xiao-Hua; Xia, Quan; Liu, Ting-Ting (Frontiers in Pharmacology, 2022)
Hydroxychloroquine (HCQ) is derivative of the heterocyclic aromatic compound quinoline, which has been used for the treatment of autoimmune diseases. The central purpose of this study was to investigate therapeutic effects and inflammatory immunological molecular mechanism of HCQ in experimental autoimmune hepatitis (AIH). Treatment with HCQ ameliorated hepatic pathologic damage, inflammatory infiltration, while promoted regulatory T cell (Treg) and down-regulated CD8+T cell differentiation in AIH mice induced by S-100 antigen. In vitro, HCQ also suppressed pro-inflammatory cytokine (IFN-γ, TNF-α, and IL-12) secretion, promoted anti-inflammatory cytokine (TGF-β1) secretion. HCQ mainly impaired T cell lipid metabolism but not glycolysis to promote Treg differentiation and function. Mechanistically, HCQ down-regulated GRK2 membrane translocation in T cells, inhibited GRK2-PI3K interaction to reduce the PI3K recruiting to the membrane, followed by suppressing the phosphorylation of PI3K-AKT-mTOR signal. Pretreating T cells with paroxetine, a GRK2 inhibitor, disturbed HCQ effect to T cells. HCQ also reversed the activation of the PI3K-AKT axis by 740 Y-P (PI3K agonist). Meanwhile, HCQ inhibited the PI3K-AKT-mTOR, JAK2-STAT3-SOCS3 and increased the AMPK signals in the liver and T cells of AIH mice. In conclusion, HCQ exhibited specific and potent therapeutic effects on AIH and attendant liver injury, which was attributed to HCQ acted on GRK2 translocation, inhibited metabolism-related PI3K-AKT and inflammation-related JAK2-STAT3 signal in T lymphocytes, thereby modulating lipid metabolism of T cell function to regulate Treg differentiation and function.